The Family And ICT - RUŽIĆ-BAF, MAJA; Kadum, Sandra; DAMIĆ, MANUELA (Journal of Education Culture and Society, 2020)
Aim. In the last three to four decades, many technological changes have taken place that have affected the world, the family and the relationships between family members. In order to determine the impact of information and communication technology on the family and its members, and how much time the research participants spend using modern technology, a survey was conducted in which 160 respondents (parents) participated.Methods. The research used a measuring instrument designed precisely for the purposes of this research. It consisted of three independent variables (gender, parental age and child's age) and nine dependent variables grouped into three sets: electronic media and time of their use, the impact of modern technology on family relationships and impact on the health of the children of the research participants. The Likert-type scale, adapted to the needs of this research, was used.Results. The research results show: the respondents' answers regarding the variable of “How much time your child spends using information and communication technologies (ICT)" are statistically significant (c2 = 48.650, p < .000); the correlation between the variables ("Gender" and "Do you talk to your children about the negative impact of ICT") is r = .180 and is significant at the .05 level; (3) the respondents' answers regarding the variable ("The knowledge of ICT in the early childhood is essential") are statistically significant (c2 = 43.438, p < .000); (4) the correlation between the variables ("The use of ICT affects family relationships" and "It affects the health of the child") is r = .194 and is significant at the .05 level.Conclusion. Children no longer live under the constant supervision of their parents, but are given the freedom to develop, think and form opinions independently. As a result, they are increasingly left to different environmental influences.